ANALISIS KESESUAIAN MATERI DENGAN KOMPETENSI PADA BUKU AJAR BAHASA SUNDA â€œPANGANTEUR BASA SUNDA PIKEUN MURID SD/MI KELAS VIâ€ - Ranu Sudarmansyah; Dingding Haerudin; Vinie Novianita (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2021)
Textbooks have a very important role in the learning process so there is a need for a conformity between the material in the textbook and the competencies in the curriculum. There had been a lot of research on the quality of textbooks. However, there was still a lack of textbooks at the elementary school level. Therefore, research on Sundanese language textbooks at the elementary school level was needed to measure the conformity of the content and the conformity of the material themes. The purpose of this study was to determine the level of conformity of the descriptions of the materials with core competencies, basic competencies & indicators. The method used in this research was descriptive analysis with literature study techniques. The data source was the textbook Panganteur Basa Sunda with 2013 Curriculum SD/ MI Class VI revised by Kanisius. From the results of the analysis, it was found that the level of conformity of (1) material descriptions with core competencies reached 75%, (2) the conformity level of material with basic competencies reached 91.5% and (3) the level of conformity of material with indicators of the competency achievement reached 85%. Thus, overall Panganteur Basa Sunda book had a good category with the level of conformity of the material with the curriculum reaching 84%. However, the conformity of the teaching instructions with the operational verbs was still lacking (72.8%). Nevertheless, overall this book was suitable to be used in Sundanese language learning in grade VI.